The letters of Jonathan Netanyahu: the commander of the Entebbe rescue force - Netanyahu, Yonatan (Gefen Pub. House, 2013)
Introduction / Herman Wouk -- Ode to Yoni / Benjamin Netanyahu -- Foreword / Benjamin and Iddo Netanyahu -- The United States, 1963-1964 -- Zahal, 1964-1967 -- Release and call-up, the Six-Day War, 1967 -- Harvard and the Hebrew University, 1967-1969 -- Zahal again, in an elite unit, 1969-1973 -- From the Yom Kippur War to Operation Jonathan, 1973-1976 -- Afterword: Yoni's last days -- Statement by General Shlomo Gazit, Chief of Israeli Military Intelligence -- Eulogy for Lt. Col. Jonathan Netanyahu: delivered by Shimon Peres, Israel's Defense Minister.